The adsorption of vinyl chloride and vinylidene chloride monomers on their polymers - Torrington, Ralph George (Department of Chemistry, 2016)
Following semi-quantitative investigations of the kinetics and equilibria of:- (a) Vinyl chloride monomer vapour adsorbed on polyvinyl chloride; (b) Vinylidene chloride monomer vapour adsorbed on polyvinyl chloride; (c) Vinylidene chloride monomer vapour adsorbed on polyvinylidene chloride; it became evident that, for a number of reasons detailed in the text, it would be worthwhile to study system (a) in detail. Thorough investigations were therefore made at the two temperatures, 25⁰ C and 42.6⁰ C, and in the pressure range 20 torr to 600 torr, with the following results: (i) Attainment of equilibrium, especially at the higher pressures, was very slow and as a result only approximate isotherms could be obtained. These isotherms were shown to exhibit hysteresis. Comparison of the amount of monomer adsorbed at the higher pressures within the above limits, with the amount of krypton required to cover the surface with a monolayer, indicated that multimolecular adsorption occurred. The ascending branches of the isotherms appeared to obey the Freundlich isotherm and the approximate isosteric heats of adsorption calculated from the equilibrium data fell off linearly as the logarithm of the amount of monomer adsorbed increased; as would be expected if the Freundlich isotherm were obeyed. The values of the heats of adsorption found were such that comparison between them and the latent heat of vapourisation of the monomer made it difficult to decide whether the first layer on the surface was chemisorbed or physically adsorbed. (ii) The kinetic data showed that there was always an initial instantaneous adsorption which was reversible towards pressure, followed by a very much slower uptake of monomer. The kinetics of the slow uptake of monomer was studied, at the two temperatures, under both constant pressure and constant volume conditions and was shown to consist of two processes.